Moist exposed burn ointment accelerates diabetes-related wound healing by promoting re-epithelialization - Gong, Yuanxun; Jiang, Yan; Huang, Jinmei; He, Zuofen; Tang, Qianli (Frontiers in Medicine, 2023)
Background: The incidence of diabetes-related wounds is widespread, and the treatment is challenging. We found that Moist Exposed Burn Ointment (MEBO) promotes the healing of diabetes-related wounds, but the mechanism is not clear. Methods: This study aimed to explore the mechanism of MEBO on diabetic wound healing, which may be related to the promotion of re-epithelialization. A full-thickness skin resection model was established in streptozotocin(STZ)-induced diabetic mice. MEBO and Kangfuxin (KFX) were applied to the wound area, and the wound healing rate was analyzed by photographing. The granulation tissue and epidermal thickness, the collagen remodeling rate, and the expression of cytokeratin 10 (CK10), cytokeratin 14 (CK14), Ki67,CollagenⅠ,and Collagen Ⅲ in the regenerated skin were detected by H&E staining, Masson staining, and immunofluorescence staining, respectively. MEBO and KFX were applied to human immortalized keratinocytes (HaCaT)、mouse dermal fibrolasts (MDF) cells, and cell viability, cell migration, and differentiation were determined by CCK-8, scratching assay, RT-qPCR, and Western blot(WB), respectively. Results: We found that MEBO significantly promoted the formation of wound granulation tissue and collagen remodeling in diabetic mice. The application of MEBO to diabetic wounds not only promoted the formation of hair follicles and sebaceous glands but also promoted the expression of Ki67, CK10, and CK14 in epidermal cells. MEBO had no significant effect on the differentiation process of keratinocytes. Conclusions: Our study further proved that MEBO plays a positive role in diabetic wound healing, and its excellent ability to promote re-epithelialization may be an important reason for promoting wound healing.